Chronology and documentary handbook of the State of Nevada - Vexler, Robert I. (Chronologies and documentary handbooks of the States, 1978)
Contains a chronology of historical events from 1775 to 1977, a biographical directory of prominent citizens, and selected documents including the State constitution of 1864.